2004
DOI: 10.1128/iai.72.1.332-337.2004
|View full text |Cite
|
Sign up to set email alerts
|

Immune Response to Meningococcal Serogroup C Conjugate Vaccine in Asplenic Individuals

Abstract: Asplenic individuals are known to be at increased risk of infection with encapsulated bacteria. Recent United Kingdom recommendations stated that this at-risk group should receive one dose of the meningococcal serogroup C conjugate (MCC) vaccine. However, the immune response of asplenic individuals to MCC vaccine is unknown. The immune response of asplenics (n ‫؍‬ 130) to immunization with the MCC vaccine was investigated. Asplenic individuals had a significantly lower geometric mean titer (GMT) (157.8; 95% co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
3
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 30 publications
1
42
3
1
Order By: Relevance
“…All 5,232 undergraduate students, as well as graduate students and faculty and staff members at increased risk for meningococcal disease, were advised to receive vaccine. Persons at increased risk were defined as persons with underlying health conditions as recommended by ACIP (3,5,6) and persons living in on-campus housing at the time of the outbreak (208 persons other than undergraduate students). During four vaccination clinics held February 4-8, a total of 4,921 persons received the first vaccine dose.…”
mentioning
confidence: 99%
“…All 5,232 undergraduate students, as well as graduate students and faculty and staff members at increased risk for meningococcal disease, were advised to receive vaccine. Persons at increased risk were defined as persons with underlying health conditions as recommended by ACIP (3,5,6) and persons living in on-campus housing at the time of the outbreak (208 persons other than undergraduate students). During four vaccination clinics held February 4-8, a total of 4,921 persons received the first vaccine dose.…”
mentioning
confidence: 99%
“…Although the quadrivalent meningococcal polysaccharide vaccine is the only meningococcal vaccine approved by the US. Food and Drug Administration for asplenic patients age 56 years or more, 78,79 patients who have undergone splenectomy-even those age 56 years or moreshould receive the quadrivalent conjugate meningococcal vaccine. 80 This recommendation is supported by data showing that in individuals who previously received a meningococcal conjugate vaccine, antibody responses to a subsequent dose of the same vaccine were higher than those to a subsequent dose of the polysaccharide quadrivalent vaccine.…”
Section: Meningococcal Vaccinementioning
confidence: 99%
“…Results from studies on vaccination of asplenic individuals with monovalent MenC conjugate vaccines [68][69][70] showed that a high proportion (~ 80 %) developed protective antibody titers, albeit a lower proportion than in healthy volunteers. A second dose of vaccine increased the proportion of responders to > 90 %.…”
Section: Potential Efficacy Of Menb Vaccination In Aspleniamentioning
confidence: 99%
“…However, the titers attained were lower than in healthy vaccinees. Persons with splenectomy due to medical conditions had lower vaccine responses than those with splenectomy due to trauma [69]. A review [71] To what extent this ability can be extrapolated to 4CMenB, however, currently remains unclear.…”
Section: Potential Efficacy Of Menb Vaccination In Aspleniamentioning
confidence: 99%